Application of Augmented Reality Technology in E-Commerce Web Applications - N Nurjamiyah; Anisa Putri; Marina Elsera (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Augmented Reality (AR), is a technology that uses the concept of combining real reality with virtual reality in real time. Augmented Reality is not the same as virtual reality capable of replacing real-world reality, but it is useful for adding or supplementing. With a 3-dimensional object inserted in the target object marker which is a special image or pattern which has been inserted by 3D image, it can be detected by the application and display a 3-dimensional image in real-time. Android smartphones can allow for AR development that can be accessed by many users and it is very easy to use. AR can be used to display products in 3 dimensions on websites of e-commerce. Augmented Reality can be used to make it easier for buyers to interact directly with products in a real way in the virtual world. The method used to design the CV.Sukses Group website was to use the MDLC (Multimedia Development Life Cycle) method which consisted of concept, design, material collecting, assembly, testing, and distribution. The results of this research were in the form of e-commerce websites, AR applications, and 3-dimensional objects. The purpose of this final project was to develop an Augmented Reality application aimed at buyers who wanted to interact directly with CV.Sukses Group products. This application was created with Unity and Vuforia Engine as AR application development tools. For websites built using a WordPress CMS. The application of Augmented Reality-based technology on the CV.Sukses Group e-commerce website could read markers on product images that would display 3-dimensional models on the screen of android devices in real-time.